Medial approach for minimally-invasive harvesting of a deep circumflex iliac artery flap for reconstruction of the jaw using virtual surgical planning and CAD/CAM technology. Issue 9 (November 2017) - Modabber, A.; Ayoub, N.; Bock, A.; Möhlhenrich, S.C.; Lethaus, B.; Ghassemi, A.; Mitchell, D.A.; Hölzle, F.
Abstract: Donor site morbidity is the most common limitation of the deep circumflex iliac artery (DCIA) flap, so the purpose of this paper is to describe a new, minimally-invasive, approach to its harvest using virtual surgical planning and CAD/CAM technology to reduce functional and aesthetic morbidity at the donor site. Virtual surgical planning was based on preoperative computed tomographic data. A newly-designed surgical guide made using CAD/CAM technology was used to transfer the virtual surgical plan to the site of operation. This enabled us to raise a bicortical flap from the pelvis with preservation of the anterior superior iliac crest from the medial side with minimal muscular stripping. The guide, designed at slightly less than 90° to the lateral cortex, allowed the cut segment of bone to be raised medially. The new virtual surgical planning guide allowed a medial approach with reduced stripping of muscle and lower morbidity. No complications were encountered during the operation or the healing phase. Patients treated in this way had a shorter recovery period, with minimal complaints about walking or loss of profile of the hip. We conclude that virtual surgical planning can aid a minimally-invasive approach with predictable results. This allows a medial approach to the harvest of DCIA with preservation of important anatomical structures, and a reduction in donor site morbidity.